2022
DOI: 10.1111/jcpt.13766
|View full text |Cite
|
Sign up to set email alerts
|

Hyperkalaemia and potassium binders: Retrospective observational analysis looking at the efficacy and cost effectiveness of calcium polystyrene sulfonate and sodium zirconium cyclosilicate

Abstract: What is Known and Objective: Hyperkalaemia is a common medical emergency in patients admitted to hospital. There is a limited evidence base supporting some of the commonly applied treatment strategies. Although, NICE has recommended the use of sodium zirconium cyclosilicate (SZC) (TA599) and patiromer (TA623) in both acute and chronic hyperkalaemia, there is a limited evidence base for their use in acute hyperkalaemia in the hospital setting, particularly when compared to the present standard of care calcium p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Huda et al have recently reported that ZSC and CPS were equally effective in reducing K + level in patients with hyperkalemia who were admitted to the hospital in an emergency, with comparable cost differences between the two groups ( 26 ). However, the differences between these two agents in potassium control and cost after an acute phase including outpatient management remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Huda et al have recently reported that ZSC and CPS were equally effective in reducing K + level in patients with hyperkalemia who were admitted to the hospital in an emergency, with comparable cost differences between the two groups ( 26 ). However, the differences between these two agents in potassium control and cost after an acute phase including outpatient management remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed reasons for down-titration and termination of SZC remain uncertain, but one of the major reasons should be the high cost of SZC. 14) This is a rationale for why we focused on the impact of SZCincorporated medical therapy for chronic heart failure and its effect on cost: Does SZC-incorporated medical therapy really increase the total medical cost? Cost-effectiveness of SZC-incorporated medical therapy: In this study, we compared the total medical costs between the SZC continue group and the SZC discontinue group.…”
Section: Discussionmentioning
confidence: 99%